Effects of differential hillslope-scale water retention characteristics on rainfall-runoff response at the Landscape Evolution Observatory - Heuvel, Daniël B. van den (Student Undergraduate Research E-journal!, 2017)
To be able to collect the reliable data necessary for understanding and modeling various Earth system processes in real catchments, controlled experiments are being conducted at the Landscape Evolution Observatory (LEO) within Biosphere2, The University of Arizona. Rainfall experiments have revealed differences in hydrological response between two landscapes within LEO, despite the landscapes’ identical design and equipment. In an attempt to discover where the observed differences stem from, we use a full 3D hydrological model (CATchment HYdrology, CATHY) to show the effect of soil water retention on the rainfall-runoff response of these two hillslopes.